Supervisi Administrasi Pada Layanan Rehabilitasi Sosial Dalam Penanganan Korban Penyalahgunaan Napza Di Sentra Galih Pakuan Bogor - Helmi Akmal Pradwika; Sokhivah Sokhivah (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2024)
Administrative supervision is very necessary to implement social rehabilitation services for victims of drug abuse. In this case, there are several things that must be researched in relation to carrying out administrative supervision, consisting of: 1) recruitment and selection of staff, 2) introduction and placement of staff, 3) work planning, 4 ) work assignment, which consists of a) understanding the assignment criteria, b) considering staff duties, c) type of assignment, d) stimulus, e) suitability of staff background with clients, 5) work delegation, 6) monitoring, reviewing and job evaluation, 6) coordination and 7) communication. This research aims to find out how administrative supervision of social rehabilitation services is in handling drug abuse victims at the Galih Pakuan Bogor Center. This research uses qualitative methods. Data collection was carried out by means of interviews, observation and documentation, determining informants using purposive sampling. The results of this research show that the supporting factors are human resources who can carry out tasks in accordance with Standard Operational Procedures at the Galih Pakuan Center and motivation for staff to be encouraged so that they want to carry out good, effective and efficient administration, the division of work groups into one supporting factors for carrying out staff performance and the existence of e-performance to provide work reports for monitoring. The inhibiting factor is the limited number of multi-service human resources and lack of capability in carrying out tasks, there are still some who do not have priority in distributing each task.